Prospective Aspect of Topography: The Example of The Grand Bazaar (Kapalı Çarşı) in Istanbul - Emre Demirel; Soufi Moazemi Goudarzi (Iconarp International Journal of Architecture and Planning, 2023)
The Grand Bazaar was constructed, there have been significant changes in shopping practices. Particularly the spread of Global trade boosted the opening of new shopping centres, high-street department stores and shopping malls. Despite all these changes in shopping habits, the Grand Bazaar still continues to be an actively used shopping area; it has never lost its customer interest and its socially vivid atmosphere. This research explores the reasons why the Grand Bazaar has not been lost its social dynamism over the course of time? This question has various answers, but this research argues that one of them is particularly related to its peculiar spatial formation that encourages social interactions. In this account; this research methodologically focuses on two main components, these are: how the Grand Bazaar was spatially constructed and how it was experienced by users. These purposes will be accomplished by the analyses of the writings and drawings of the important Western travellers. It is revealed that articulated in topographical account, the Grand Bazaar eliminates the boundaries between the spaces and thus between the people. This continually enhances the mutual relationships between inside and outside. This study focuses on the main interest of the topographic approach which is not much the representative qualities; re-expression of the exterior appearance of the building in shape and profile or any stylistic display, but it is more to create an open venue or a stage which enhances the spatial and social connectivity between interior and exterior worlds, ergo between individual and collective lives. As a result, the study demonstrates how the Grand Bazaar's topographical attitude lends a 'formative' aspect to an architectural context. The Grand Bazaar tries to abolish borders by emphasizing topographical aspects such as permeability, spatiality, and delay in order to create an in-between environment, and also a common social ground.